Studies of the species barrier between Drosophila subobscura and D. madeirensis. III. How universal are the rules of speciation? - Khadem, Mahnaz (2021)
The prevalence of Haldane's rule and the large effect of the X chromosome are examined by analysing the genetics of seven abnormal characters in interspecies hybrids between D. subobscura and D. madeirensis. In two cases Haldane's rule is not obeyed (viability and abnormality of the head). In all characters except the abnormal abdominal tergites, an important effect of the X chromosome is observed. There is an asymmetry in the importance of the effect of the X chromosome. The X of D. madeirensis origin induces abnormality mostly in a mixed background. TheY chromosome plays an important role in determining male sterility.